Ancestry‐specific intronic variants on the APOEɛ4 haplotype influence enhancer activity and interaction with APOE promoter. (1st February 2022) - Nuytemans, Karen; Vasquez, Marina Lipkin; Rajabli, Farid; Celis, Katrina; Oron, Oded; Van Booven, Derek; Hofmann, Natalia K.; Argenziano, Mariana; Chesi, Alessandra; Grant, Struan F.A.; Brown, Christopher D.; Griswold, Anthony J.; et al.
Abstract: Background: The risk for late‐onset Alzheimer disease (AD) in APOEε4 carriers differs between ancestral groups, where APOEε4's odds ratio for AD risk is lower in African (AFR) homozygous carriers than in non‐Hispanic White (NHW) or Japanese (JPT) carriers (odds ratio ∼2‐5 vs >15). Local ancestry (LA) analyses in APOEε4 carrier populations have shown the protective effect in AFR relative to EUR/JPT is due to noncoding factors lying in the LA surrounding APOEε4 . Thus, regulatory differences between risk and protective LA haplotypes are most likely involved in the differential risk effect seen for APOEε4 on different backgrounds. Methods: We identified 56 significant sequence differences between AFR and EUR/JPT APOEε4 haplotypes from the 1000 genomes in the immediate topologically associated domain surrounding APOE . We performed two different Massively Parallel Reporter Assay (MPRA) designs; one assessing small haplotype (∼900bp) effects and one based upon single variant effects. We supplemented these results with single fragment luciferase reporter assays. All assays were performed in at least duplicate in HMC3 (microglia), U118 (astrocytes) and SH‐SY5Y (neurons) cell lines. Additionally, we integrated chromatin interaction information from promoter capture C chromatin conformation assays in the same cell types. Results: We identified a region in the first introns of TOMM40 with increased EUR/JPT enhancer activity, supported by both MPRA analyses and APOE promoter interaction in astrocytes and microglia. Two additional regions with differential enhancer activity in neurons, but no promoter interaction, were identified; downstream of APOE and in PVRL2 introns upstream of APOE presenting with higher EUR or higher JPT haplotype variant enhancer activity compared to AFR, respectively. Conclusions: Our results indicate several areas of differential regulation in this LA region on APOEε4 haplotypes dependent on cell type. As APOE is mostly expressed in glial cells, the data in TOMM40 introns points to this region as having the biggest impact on APOE expression in our study and thus highly supports the involvement of this region in the differential risk effects seen for APOEε4 . Follow‐up of the identified regulatory regions is currently ongoing using in‐house iPSC derived cell lines.